The effect of knowledge on uptake of breast cancer prevention modalities among women in Kyadondo County, Uganda - Christine Atuhairwe; Dinah Amongin; Elly Agaba; Steven Mugarura; Ivan M. Taremwa (BMC, 2018)
Abstract Background Breast cancer, the third most frequent cancer of women is preventable through knowledge on breast self-examination. Of the 44% of women diagnosed with breast cancer at the Uganda Cancer Institute, only 22% go for check-up in less than three months. This study explored the effect of breast cancer knowledge on the uptake of breast cancer prevention modalities among women in Kyadondo County, Uganda. Methods A household survey of women in Kyadondo County was conducted during June, 2014 to August, 2015. This involved studying in-depth using a questionnaire the level of breast cancer knowledge of the respondents. Data was analyzed using logistic regression model. Chi-square test was used to establish relationships between knowledge base factors and the uptake of breast cancer prevention modalities. Results This study has established an empirical relationship between uptake of breast cancer prevention modalities and source of information especially radio (OR 1.94 95% CI: 1.16-3.24), television (OR 1.82 95%CI: 1.14-2.93), awareness of breast cancer (OR 4.03 95%CI: 1.01-15.98), knowledge on how to reduce risk of breast cancer (OR 1.98 95% CI: 1.20-3.27), what reduces breast cancer acquisition (OR 2.75 95% CI: 1.42-5.35), how to check for signs of breast cancer especially through breast self-examination (OR 3.09 95% CI: 1.62-5.88), and other methods of breast cancer diagnosis in a health care set up. Conclusion The women's level of breast cancer awareness as a primary prevention strategy was found wanting, and requires a boost through community health education.